Skiing Trauma and Safety: Thirteenth Volume 2000
DOI: 10.1520/stp12867s
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of ACL Ruptures in French Ski Resorts 1992–1999

Abstract: This work done by 72 French doctors in the “Médecins de Montagne” skiing safety network studies the evolution of the rate of ACL ruptures since 1992. The study was done on 232 571 injuries including 21 303 ACL ruptures. Alpine skiing ACL ruptures, which have been increasing since 1992, represent 12.5% of accidents (3125 MDBI). A control group is analyzed each season through interviews at the bottom of the slopes in parking lots and random evaluations. We have ascertained that ACL ruptures repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 11 publications
1
21
0
2
Order By: Relevance
“…These findings align with earlier studies [5][6][7][8]. Since the introduction of the carving ski in 1993, female skiers have dominated knee injury trends.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with earlier studies [5][6][7][8]. Since the introduction of the carving ski in 1993, female skiers have dominated knee injury trends.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, the present data on freestyle skiing show no sex difference in the absolute or relative injury risk. Several studies have reported a twofold greater rate of knee injuries among female recreational skiers,14 2931 while the rate of shoulder, spine and head injuries has been shown to be higher in male skiers 14 29 3234. However, no sex differences were found in the rate of knee injuries among WC Alpine skiers 10.…”
Section: Discussionmentioning
confidence: 96%
“…A common skiing injury is anterior cruciate ligament (ACL) rupture (Gianotti, Marshall, Hume, & Bunt, 2008;Johnson, 1995), comprising 20-30% of all skiing injuries (Laporte, Binet, & Constans, 2000;Pujol, Blanchi, & Chambat, 2007). Anterior cruciate ligament injuries are often linked to stiff landings from a jump in a flexed knee posture during highspeed downhill skiing (Ettlinger, Johnson, & Shealy, 1995;Figueras, Escalas, & Vidal, 1987).…”
Section: Introductionmentioning
confidence: 99%